Antibiotic Profiling of Heavy Metal Resistant Bacterial Isolates from the Effluent of a Garment Industry in Lalitpur, Nepal - Sharma, M.; Thapaliya, H.P. (Our Nature, 2010)
Heavy metal resistant bacterial isolates from the effluent in a garment industry site were examined to assess their resistance towards multiple antibiotics. Heavy metal resistance property has been found to enhance the antibiotic resistance ability of microorganisms. Isolation of the heavy metal resistant organisms was done in media containing salts of heavy metals. Organisms were identified belonging to the genera Bacillus, Corynebacterium, Lactobacillus, Aeromonas and Enterococcus. Bacterial isolates were tested for their sensitivity to seven common antibiotics (penicillin, tetracycline, erythromycin, chloramphenicol, gentamicin, vancomycin and cotrimoxazole) using Kirby-Bauer technique. Isolates were found to be resistant to multiple antibiotics but all the isolates were sensitive to gentamicin. The data of our study indicates that metal pollution of the environment is the cause of heavy metal resistance isolates and hence antibiotic resistance. Key words: Heavy metal, effluent, antibiotics, resistance, Bacteria, pollution. DOI: 10.3126/on.v7i1.2572 Our Nature (2009) 7:203-206